Effects of supplementation with main coffee components including caffeine and/or chlorogenic acid on hepatic, metabolic, and inflammatory indices in patients with non-alcoholic fatty liver disease and type 2 diabetes: a randomized, double-blind, placebo-controlled, clinical trial - Mansour, Asieh (Nutr J, 2021)
BACKGROUND: Non-alcoholic fatty liver disease (NAFLD) is much more frequent and more severe, including cirrhosis, hepatocellular carcinoma in patients with type 2 diabetes. Coffee is a complex beverage with hundreds of compounds whereas caffeine and chlorogenic acid are the most abundant bioactive compounds. The published epidemiological data demonstrating beneficial associations between all categories of coffee exposure and ranges of liver outcomes are rapidly growing; however, the main contributors and cause-effect relationships have not yet been elucidated. To address existing knowledge gaps, we sought to determine the efficacy and safety of 6 months chlorogenic acid and/or caffeine supplementation in patients with type 2 diabetes affected by NAFLD. METHODS: This trial was carried out at two Diabetes Centers to assess the effects of supplementation with daily doses of 200 mg chlorogenic acid, 200 mg caffeine, 200 mg chlorogenic acid plus 200 mg caffeine or placebo (starch) in patients with type 2 diabetes and NAFLD. The primary endpoint was reduction of hepatic fat and stiffness measured by FibroScan, and changes in serum hepatic enzymes and cytokeratin − 18 (CK-18) levels. Secondary endpoints were improvements in metabolic (including fasting glucose, homeostasis model assessment-estimated insulin resistance (HOMA-IR), hemoglobin A1c (HBA1C), C-peptide, insulin and lipid profiles) and inflammatory (including nuclear factor k-B (NF-KB), tumor necrosis factor (TNF-α), high sensitive- C reactive protein(hs-CRP)) parameters from baseline to the end of treatment. RESULTS: Neither chlorogenic acid nor caffeine was superior to placebo in attenuation of the hepatic fat and stiffness and other hepatic outcomes in patients with diabetes and NAFLD. Except for the lower level of total cholesterol in caffeine group (p = 0.04), and higher level of insulin in chlorogenic acid plus caffeine group (p = 0.01) compared with placebo, there were no significant differences among the treatment groups. CONCLUSION: These findings do not recommend caffeine and/or chlorogenic acid to treat NAFLD in type 2 diabetes patients. TRIAL REGISTRATION: IRCT201707024010N21. Registered 14 September 2017.